Electronic structure and chemical bonding in transition-metal-mixed gallium oxide (Ga2O3) compounds. (October 2021) - Ramana, C.V.; Roy, Swadipta; Zade, Vishal; Battu, Anil K.; Makeswaran, Nanthakishore; Shutthanandan, V.
Abstract: Transition metal (TM)-mixed gallium oxide (Ga2 O3 ) ceramic compounds have potential applications in optical, optoelectronic, and photovoltaic devices. Herein, we report on the salient electronic structures and chemical properties of a series of such compounds, with a view to optimizing performance. The TM-mixed Ga2 O3 (Ga2- x M x O3 ; TM-GO; 0.0 ≤  x  ≤ 0.3, M = Fe, Ti, W) polycrystalline compounds were synthesized by a conventional, high-temperature solid-state reaction method. The effects of Fe-, Ti-, and W-doping on the electronic structures of the TM-GO compounds have been studied. The chemical states of Fe, Ti, and W ions in the TM-GO compounds vary as a function of TM concentration. The electronic structures and chemical states of the respective ions are greatly modified when Fe, Ti, or W ions are mixed in Ga2 O3 . For Fe and W, mixed chemical states (Fe 2+ /Fe 3+, W 4+ /W 6+ ) are evident in single-phase TM-GO compounds for lower x . On the contrary, Ti ions are invariably in their highest oxidation state (Ti 4+ ) for all x in Ti-mixed-Ga2 O3 compounds. Irrespective of the TM dopant, Ga ions exist in their highest oxidation state (Ga 3+ ). The fundamental scientific understanding of the electronic properties, and tunability thereof, of TM-GO compounds presented in this detailed study should be useful when considering them for application in electronic, optoelectronic, or energy devices, or related technological fields. Graphical abstract: Image 1 Highlights: Tunable electronic properties are demonstrated in transition-metal-doped Ga2 O3 . Ga2- x M x O3 (0.0 ≤  x  ≤ 0.3, M = Fe, Ti, W) compounds have been synthesized by solid-state reaction. The electronic structure is greatly modified when Fe, Ti, or W ions are doped in Ga2 O3 . Fe and W exhibit mixed chemical states (Fe 2+ /Fe 3+, W 4+ /W 6+ ), whereas Ti is invariably present as Ti 4+ . The electrochemical activity of doped Ga2 O3 indicates its application potential in energy technologies.